GAMBARAN KUALITAS HIDUP PADA PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISIS DI RSUD MEURAXA KOTA BANDA ACEH - Shakila, Syarifah Nurul; Said Aandy Saida; Elmiyati (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
Chronic kidney failure (CKD) is a huge and increasing public health problem. One of the actions performed on CKD patients is hemodialysis. The quality of life of CKD patients is closely related to hemodialysis. However, hemodialysis is not a therapy for recovery. Hemodialysis is performed to maintain the life and well-being of the patient until kidney function is restored. This study aims to describe the quality of life in CKD patients undergoing hemodialysis at Meuraxa Hospital, Banda Aceh City. This study used an observational method with a cross sectional approach. The number of samples is 58 respondents taken by using accidental sampling technique. The measurement of quality of life uses the WHOQOL-BREF questionnaire. The results of this study showed that in terms of characteristics, the highest age was at the age of 56 to 65 years with 34 respondents (58.6%) and no respondents in the age range of 18 to 25 years. In terms of gender, the highest was female with 32 respondents (55.2%) and the lowest was male with 26 respondents (44.8%). In the quality of life of CKD patients undergoing hemodialysis at Meuraxa Hospital, Banda Aceh City, the highest was in the bad category, 32 respondents (55.2%) and the lowest was in the very good category, 1 respondent (1.7%).